The Influence of Strategic Management and Organizational Culture on Teacher Employee Engagement - Wahyudin Wahyudin; Rina Mida Hayati; Choirudin Choirudin (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the influence of strategic management and organizational culture on teacher employee engagement at MAN 2 Tulang Bawang Barat, both partially and simultaneously. The research background is based on the phenomenon of low teacher discipline, role modeling, and integrity according to the 2024 Integrity Assessment Survey (SPI) by the Corruption Eradication Commission (KPK), indicating weak teacher work engagement. The study employed a quantitative approach with a survey method. The population consisted of all 40 permanent teachers at MAN 2 Tulang Bawang Barat, selected using total sampling technique. The research instrument was a Likert scale questionnaire (1–5) that had been tested for validity and reliability. Data analysis techniques included descriptive statistics and multiple linear regression using SPSS. The results showed that: (1) the level of strategic management implementation was in the high category (mean = 82.48); (2) the level of organizational culture was in the medium category (mean = 79.25); (3) the level of teacher employee engagement was in the medium category (mean = 77.15); (4) strategic management had a partial and significant effect on employee engagement (t = 4.629, sig. = 0.000); (5) organizational culture had a partial and significant effect on employee engagement (t = 4.667, sig. = 0.000); (6) strategic management and organizational culture simultaneously had a significant effect on employee engagement (F = 28.742, sig. = 0.000) with a contribution of 60.8% (R² = 0.608). This study recommends strengthening teacher involvement in strategic planning and enhancing the culture of innovation in madrasahs.